Visual Phenomenology - Madary, Michael (Book collections on Project MUSE., 2017)
"In this book, Michael Madary examines visual experience, drawing on both phenomenological and empirical methods of investigation. He finds that these two approaches--careful, philosophical description of experience and the science of vision--independently converge on the same result: Visual perception is an ongoing process of anticipation and fulfillment. Madary first makes the case for the descriptive premise, arguing that the phenomenology of vision is best described as on ongoing process of anticipation and fulfillment. He discusses visual experience as being perspectival, temporal, and indeterminate; considers the possibility of surprise when appearances do not change as we expect; and considers the content of visual anticipation. Madary then makes the case for the empirical premise, showing that there are strong empirical reasons to model vision using the general form of anticipation and fulfillment. He presents a range of evidence from perceptual psychology and neuroscience, and reinterprets evidence for the two-visual-systems hypothesis. Finally, he considers the relationship between visual perception and social cognition. An appendix discusses Husserlian phenomenology as it relates to the argument of the book. Madary argues that the fact that there is a convergence of historically distinct methodologies itself is an argument that supports his findings. With Visual Phenomenology, he creates an exchange between the humanities and the sciences that takes both methods of investigation seriously"--Publisher's website.